Estimating the prevalence of COPD in an African country: evidence from southern Nigeria - Boni M. Ale; Obianuju B. Ozoh; Muktar A. Gadanya; Yiyang Li; Michael O. Harhay; Akindele O. Adebiyi; Davies Adeloye (Journal of Global Health Reports)
# Background